Bright futures : guidelines for health supervision of infants, children, and adolescents : pocket guide - Hagan, Joseph F., Jr; Shaw, Judith S.; Duncan, Paula M. (American Academy of Pediatrics, 2017)
This essential resource developed by multidisciplinary panels of experts in infancy, early childhood, middle childhood, and adolescent health (i.e., pediatricians, family physicians, nurse practitioners, nutritionists, mental health specialists, pediatric dentists and families), covers 12 health promotion themes including: Promoting Family Support, Promoting Healthy Weight, and more! The guidelines reflect updated AAP Recommendations for Preventive Pediatric Health Care, updates to content reflected in the 32 health supervision visits (prenatal and 31 well-child care visits). New themes include: Promoting Lifelong Health for Families and Communities; Promoting Health for Children and Youth with Special Health Care Needs; Promoting the Healthy and Safe Use of Social Media. -- Provided by publisher.